Synthesis, Characterization and Optical Properties of BaMoO4Synthesized by Microwave Induced Plasma Method - Arrak Klinbumrung (2018)
© 2018, Pleiades Publishing, Ltd. BaMoO4crystals were synthesized by a 900 W microwave induced plasma process (MIP) for 40, 60, 120 and 140 min. Phase, morphology, vibrational mode and energy gap were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), photoluminescence (PL) spectroscopy, Fourier transform infrared (FTIR) spectroscopy and UV-visible spectroscopy. In this research, the phase and morphology of product were influenced by microwave heating time. The sample processed for 140 min shows spherical particles tetragonal BaMoO4phase with size of 200–700 nm in diameter. BaMoO4with band gap of 3.35 eV shows a blue emission wavelength at 440 nm.